UV irradiation of Cu-based complexes with aliphatic amine ligands as used in living radical polymerization. (15th January 2020) - Liarou, Evelina; Staniforth, Michael; Town, James S.; Marathianos, Arkadios; Grypioti, Maria; Li, Yongguang; Chang, Yujing; Efstathiou, Spyridon; Hancox, Ellis; Wemyss, Alan M.; Wilson, Paul; Jones, Bryn A.; et al.
Graphical abstract: Highlights: Excited-state dynamics of Cu(II)-based complexes as used in Cu-RDRP. Investigation of the photo-redox behaviour of the catalyst complexes. Detection of different species upon complexation of the ligand to the metal center. Effect of different amine ligands on photoinduced Cu-RDRP. Abstract: The effect UV irradiation on Cu(II)-based complexes with aliphatic amine ligands is investigated. Four aliphatic amines are used as ligands and Cu(II)Br2 as the metal source for the formation of catalyst complexes that can be used for the photoinduced Cu-RDRP of methyl acrylate. Different characterization techniques such as transient electronic absorption spectroscopy (TEAS), ultraviolet–visible (UV–Vis) spectroscopy, electrospray ionization time of flight mass spectrometry (ESI-ToF-MS) and cyclic voltammetry (CV) are applied in order to provide insights into the catalyst behaviour upon photo-irradiation. The excited-state dynamics, the electrochemical behaviour of the Cu(II)/Cu(I) redox couples and the detection of different species upon complexation of the ligand to the metal center (before and after UV irradiation) are further depicted in the quality of the obtained polymers.